Hubungan antara Gaya Humor dengan Persepsi Mahasiswa terhadap Efektivitas Mengajar Dosen dalam Pembelajaran Jarak Jauh - Desmiyati Desmiyati; Erik Wijaya; Kurniati W. Andani (Fakultas Psikologi Universitas Tarumanagara, 2022)
During COVID-19 pandemic, learning activities were carried out online at home using online media. According to the college student's point of view, distance learning is considered less effective and boring so that using humor in the teaching and learning process is considered to increase the teaching effectiveness of lecturers in the classroom. Therefore, this study aims to determine the relationship between humor style and collage student’s perceptions of the teaching effectiveness of lecturers in distance learning. This research is quantitative research using non-probability sampling techniques, namely convenience sampling and snowball sampling. Participants in this study were 396 college students with age range of 18-25 years old. The measuring instrument used in this research were Humor Styles Questionnaire (HSQ) from Martin et al. (2003) which has been adapted into Indonesian by Laia (2014) and Teaching Effectiveness Scale (TES) from Calaguas (2013). The results of this study indicated that there was a positive and significant relationship between humor style on the self-enhancing humor dimension and teaching effectiveness in terms of the college student’s perceptions with a value of r = .287, p = .000 < .05. Other results show that the self-enhancing humor dimension has a positive and significant relationship with variables of teaching effectiveness on the dimensions of personality, subject matter expertise, relational competence with students, professional competence, teaching style, and classroom management style. This means, the higher the lecturer's self-enhancing humor, the higher teaching effectiveness of lecturer.